Purely Off-Clamp Laparoscopic Partial Nephrectomy Stands the Test of Time: 15 Years Functional and Oncologic Outcomes from a Single Center Experience - Aldo Brassetti; Umberto Anceschi; Alfredo Maria Bove; Francesco Prata; Manuela Costantini; Mariaconsiglia Ferriero; Riccardo Mastroianni; Leonardo Misuraca; Gabriele Tuderti; Giulia Torregiani; Marco Covotta; Michele Gallucci; et al. (Current Oncology, 2023)
Background: Nephron-sparing surgery represents the gold standard treatment for organ-confined renal tumors. We present 15-years of outcomes after off-clamp laparoscopic partial nephrectomy (ocLPN). Methods: a retrospective analysis was performed on patients who underwent ocLPN between May 2001 and December 2005. Baseline demographic, clinical, pathologic, surgical, functional and survival data were collected. The Kaplan–Meier method evaluated group-specific oncologic outcomes at 5, 10 and 15 years and the log rank test assessed differences between groups. The same analysis investigated the probabilities of developing a significant renal function impairment (sRFI) and achieving ROMeS. Cox analyses identified predictors of this latter tricomposite outcome. Results: We included 63 patients whose median tumor size was 3 cm (IQR:2–4). At 15 years, the chances of developing local recurrence, metachronous renal cancers or distant metastases were 2 ± 2%, 23 ± 6% and 17 ± 5%, respectively. Consequently, disease-free, cancer-specific and overall-survival probabilities were 68 ± 6%, 90 ± 4% and 72 ± 6%. MCRSS and UCISS well predicted oncologic outcomes. Overall, nine (14%) patients experienced an sRFI and 33 (52%) achieved ROMeS. Age (HR: 1.046; p = 0.033) and malignant histology (low-risk cancers HR: 3.233, p = 0.048) (intermediate/high risk cancers HR: 5.721, p = 0.023) were independent predictors of ROMeS non-achievement. Conclusions: At 15 years from ocLPN, most of patients will experience both excellent functional and oncologic outcomes.